The SILCC project: III. Regulation of star formation and outflows by stellar winds and supernovae - Gatto, Andrea; Glover, Simon; Klessen, Ralf S.; Baczynski, Christian (Monthly notices of the Royal Astronomical Society, 2017)
We study the impact of stellar winds and supernovae on the multiphase interstellar medium using three-dimensional hydrodynamical simulations carried out with flash. The selected galactic disc region has a size of (500 pc)2 × ±5 kpc and a gas surface density of 10 M⊙ pc−2. The simulations include an external stellar potential and gas self-gravity, radiative cooling and diffuse heating, sink particles representing star clusters, stellar winds from these clusters that combine the winds from individual massive stars by following their evolution tracks, and subsequent supernova explosions. Dust and gas (self-) shielding is followed to compute the chemical state of the gas with a chemical network. We find that stellar winds can regulate star (cluster) formation. Since the winds suppress the accretion of fresh gas soon after the cluster has formed, they lead to clusters that have lower average masses (102-104.3 M⊙) and form on shorter time-scales (10−3-10 Myr). In particular, we find an anticorrelation of cluster mass and accretion time-scale. Without winds, the star clusters easily grow to larger masses for ∼5 Myr until the first supernova explodes. Overall, the most massive stars provide the most wind energy input, while objects beginning their evolution as B-type stars contribute most of the supernova energy input. A significant outflow from the disc (mass loading ≳1 at 1 kpc) can be launched by thermal gas pressure if more than 50 per cent of the volume near the disc mid-plane can be heated to T > 3 × 105 K. Stellar winds alone cannot create a hot volume-filling phase. The models that are in best agreement with observed star formation rates drive either no outflows or weak outflows.
Published: 12 December 2016
Gesehen am 04.04.2018